Tokyo's Emissions Trading System : A Review of its Operation since 2010 - World Bank (World Bank, Washington, DC, 2016)
This note reviews the operations and experience of Tokyo's emissions trading system since its launch in 2010 and follows on from an earlier issue of directions in urban development that described the design and development process of the system. In January 2013, the Tokyo Metropolitan Government (TMG) announced that FY2011-the second full year of Emissions Trading System (ETS) operation from April 2011 to March 2012-saw a 23 percent reduction in the emissions from participating facilities covered by the ETS, compared with the base year. Total emissions from these facilities in FY2011 were 7.22 million tons of CO2, which was some 2.16 million tons less than the base year. Notably, 93 percent of these facilities achieved reductions in excess of their obligations for the first compliance period in FY2011. This surpassed the first year performance recorded in FY2010, where emissions were 13 percent below the base year, with 64 percent of facilities achieving reductions in excess of obligations for the first compliance period. Under Tokyo's ETS, facilities that reduce emissions below the target may sell the excess reductions as credits. Conversely, if actual emissions reductions fall short of the target, they may purchase credits to make up the difference. Apart from excess emissions reductions, eligible credits include offsets from small and medium sized facilities, large facilities outside Tokyo, renewable energy credits, and credits from Saitama prefectures ETS. TMG has provided a framework for long-term goal setting by indicating the estimated emissions reductions that would be required in the second compliance period.